2012
DOI: 10.3109/s10165-011-0531-7
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and attitudes toward therapy in patients with rheumatoid arthritis

Abstract: We examined associations between patient satisfaction and data obtained in routine clinical practice, and associations with therapeutic attitude in patients with rheumatoid arthritis (RA). A total of 220 patients with RA were enrolled in this cross-sectional evaluation. Demographic data, current disease state of RA, history of adverse events and self-reported questionnaire of patient satisfaction, attitudes toward therapy and reasons for being unwilling to change therapy were collected and analyzed. Multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Prior studies have also hypothesized that the fear of medication side effects and a loss of control may be factors in the unwillingness to change [7, 8, 11, 2527]. Furthermore, many patients do not want to change their therapy as long as their condition remains stable and does not worsen, even if a treatment change might result in them having improved QoL [10, 11]. The current study also indicates that patients who had previous or current bDMARD experience reported similar treatment satisfaction compared with those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also hypothesized that the fear of medication side effects and a loss of control may be factors in the unwillingness to change [7, 8, 11, 2527]. Furthermore, many patients do not want to change their therapy as long as their condition remains stable and does not worsen, even if a treatment change might result in them having improved QoL [10, 11]. The current study also indicates that patients who had previous or current bDMARD experience reported similar treatment satisfaction compared with those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi mentioned that PROs may contribute to better communicate between clinicians and patients, and guide treatment decisions [34]. PROs play a critical role in determining treatment pathways and timing of treatment [35].…”
Section: Discussionmentioning
confidence: 99%